1982
DOI: 10.1111/j.1365-2591.1982.tb01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors promoting the tissue dissolving capability of sodium hypochlorite

Abstract: EA 157, Metrohm, Herisau, Switzerland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
290
0
30

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(337 citation statements)
references
References 25 publications
10
290
0
30
Order By: Relevance
“…The disinfecting properties of hypochlorite solutions decrease with increasing pH, whereas their antimicrobial efficacy increases with decreasing pH. 15 Moorer and Wesselink found that mechanical agitation with NaOCl is very important for the generation of a tissue-dissolving effect (9). Ultrasonic agitation increased the activity of a 5% NaOCl solution in the apical third of the root canal wall (16).…”
Section: Sodium Hypochlorite (Naocl)mentioning
confidence: 99%
See 1 more Smart Citation
“…The disinfecting properties of hypochlorite solutions decrease with increasing pH, whereas their antimicrobial efficacy increases with decreasing pH. 15 Moorer and Wesselink found that mechanical agitation with NaOCl is very important for the generation of a tissue-dissolving effect (9). Ultrasonic agitation increased the activity of a 5% NaOCl solution in the apical third of the root canal wall (16).…”
Section: Sodium Hypochlorite (Naocl)mentioning
confidence: 99%
“…High concentrations of NaOCl have better tissue-dissolving effects. Low concentrations used in high volumes have potency equivalent to that of high concentrations (9). In addition, higher concentrations of NaOCl are more toxic than lower concentrations (10).…”
Section: Sodium Hypochlorite (Naocl)mentioning
confidence: 99%
“…Therefore, it may be suggested that there may be a point of saturation and the increase in volume beyond which bacterial elimination in the complex root canal space will no longer improve (28). In addition, Moorer and Wesselink (30) found that chlorine, which is responsible for the antimicrobial effect of NaOCl, is consumed rapidly within 2 min, so the time of 45 s is probably too short for the effective antimicrobial efficacy of 3% NaOCl against 21 days old E. faeaclis colonization.…”
Section: Sukob Interesamentioning
confidence: 99%
“…Esta última promovendo além do arrasto de irritantes; restos de sangue; detritos e raspas de dentina, tanto da câmara pulpar quanto dos canalículos dentinários. (FIGDOR; SUNDQVIST, 2007;HAAPASSALO et al 2005;LOPES & SIQUEIRA JR, 2004;MOORER;WESSELINK, 1982).…”
Section: O Instrumento Não Tocou-------------------------------------unclassified
“…Outros fatores relacionados à irrigação podem influenciar na eficácia da solução tais como: volume; profundidade de penetração da agulha de irrigação; tempo de permanência da solução no interior do canal radicular; área de contato e, aquecimento da solução, que no caso do hipoclorito de sódio, potencializa a dissolução de tecido orgânico (ALBRECHT; ESTRELA et al, 2002;GAMBARINI, 1999;MOORER;WESSELINK, 1982;WALTERS et al, 2002).…”
Section: O Instrumento Não Tocou-------------------------------------unclassified